Trace level determination of Δ9‐tetrahydrocannabinol in a perfume using liquid chromatography high resolution tandem mass spectrometry and gas chromatography mass spectrometry. (28th September 2016) - Thalhamer, Bernhard; Himmelsbach, Markus; Buchberger, Wolfgang
Abstract: Δ9‐tetrahydrocannabinol (Δ9‐THC), which is the primary psychoactive ingredient in marijuana, was identified at trace levels in a perfume whose name/brand and its scent aim to arouse associations with marijuana/hashish. The presence of Δ9‐THC was unambiguously confirmed by high performance liquid chromatography (HPLC) coupled with Orbitrap high resolution mass spectrometric detection. The relevant HPLC peak of the analysed perfume shows identical chromatographic behaviour and mass spectrometric fragmentation compared to an authentic reference material of Δ9‐THC. Electrospray ionization was performed in the positive mode, fragmentation was carried out by both collision‐​induced dissociation and higher‐energy collisional dissociation. The quantitation of Δ9‐THC in the complex perfume matrix was performed by HPLC combined with a triple quadrupole mass spectrometer (HPLC‐MS/MS) in the multiple reaction monitoring mode. Calibration by the standard addition method yielded a concentration of 0.2 µg Δ9‐THC per ml perfume. Additionally gas chromatography mass spectrometry was also used to confirm the results for Δ9‐THC. It is based on a fundamentally different separation principle and results were in good agreement with HPLC‐MS/MS, which proved the reliability of the analysis. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Δ9‐Tetrahydrocannabinol (Δ9‐THC) was identified at trace levels in a perfume offered in the high price segment. The presence of Δ9‐THC was unambiguously confirmed by high performance liquid chromatography (HPLC) coupled with Orbitrap high resolution mass spectrometric detection. The relevant HPLC peak of the analysed perfume shows identical chromatographic behavior and mass spectrometric fragmentation compared to an authentic reference material of Δ9‐THC. Additionally gas chromatography mass spectrometry was also used to confirm the results.